The effect of knowledge types on hybrid cars preferences - Hasan Basri, Bakti; Bakar, Normizan (2016)
Choices on products comes from various factors and knowledge is one of them. When choosing a product consumers are using either subjective knowledge or objective knowledge. And some of them want to use a combination the knowledge. In this paper, we investigate the effect of knowledge types on Hybrid Car (HCs) attributes preferences. The Choice Modelling technique is used where the six attributes chosen for the study were driving range; hybrid battery warranty period; government incentives; CO2 emission level; source of energy; and engine’s sound. A total of 242 respondents in Kedah and Perlis were interviewed but only 197 were usable for analysis. The results show that the respondents who acquired subjective knowledge are more preferred on the HCs attributes compared to those who have objective knowledge. The results provide some useful information on policy implication in marketing innovation.